2019
DOI: 10.1590/1806-9282.65.11.1374
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of clinical characteristics and prognostic of adult patients admitted to an intensive care unit

Abstract: SUMMARY OBJECTIVE: To evaluate seasonal variations of clinical characteristics, therapeutic resource use, and outcomes of critically ill patients admitted to an intensive care unit. METHODS: A retrospective cohort study conducted from January 2011 to December 2016 in adult patients admitted to the intensive care unit (ICU) of a University Hospital. Data were collected on the type of admission, APACHE II, SOFA, and TISS 28 scores at ICU admission. Length of hospital stay and vital status at hospital discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Of the 27 eligible studies ( Table 2 ), 18 were descriptive, with a quantitative and retrospective approach, ( 15 , 17 - 20 , 24 , 26 - 28 , 30 - 32 , 34 - 39 ) and seven were prospectively performed. ( 14 , 16 , 22 , 23 , 25 , 29 , 40 ) Data from all studies were collected from patient records, sector record books, and computerized database systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 27 eligible studies ( Table 2 ), 18 were descriptive, with a quantitative and retrospective approach, ( 15 , 17 - 20 , 24 , 26 - 28 , 30 - 32 , 34 - 39 ) and seven were prospectively performed. ( 14 , 16 , 22 , 23 , 25 , 29 , 40 ) Data from all studies were collected from patient records, sector record books, and computerized database systems.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic interventions applied to critically ill patients have rarely been addressed in studies. The use of IMV was evaluated in eight studies, ( 14 , 16 , 23 - 25 , 31 , 38 , 40 ) in which it was used in 10.7% to 74.3% of patients. The use of vasoactive drugs was addressed in five studies, ( 23 - 25 , 38 , 40 ) and renal replacement therapy was addressed in only three studies ( 14 , 39 , 40 ) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are studies in the literature which have reported that seasonal effects can have an impact on surgical outcomes, may increase hospital presentations, and could have positive or negative effects on the use of resources. It has been shown that seasonal status does not only affect burns patients, but can also affect breast cancer recurrence (8), high HbA1c levels (9), cardiopulmonary arrest (10), and admission to intensive care units (ICU) (11). Knowledge of these types of conditions can allow planning of resources and personnel in hospitals, ICUs, and burns centers, and even the provision of information to the community on this subject using mass communication tools.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, We were lucky enough to read the study by Galvão et al 1 in which they demonstrated that summer months presented a higher proportion of clinical and emergency surgery patients with higher mortality rates and sepsis at intensive care unit admission did not show seasonal behavior. This study shows us the year pattern of emergency surgery, which is of great reference value for disease prevention and treatment.…”
Section: Commentarymentioning
confidence: 99%